Pathways to strengthen the quality of public service delivery in Uganda: Barazas as citizen advocacy forums - Van Campenhout, Bjorn; Nabwire, Leocardia; Walukano, Wilberforce; Kabunga, Nassul Ssentamu; Bizimungu, Emmanuel; Smart, Jenny (International Food Policy Research Institute, 2019)
Studies on governance show that the provision of information and the involvement of beneficiaries in project monitoring can significantly improve both the quantity and the quality of local public service delivery. Drawing on findings from a qualitative impact assessment of barazas, this policy note provides evidence on the impact pathways through which beneficiary involvement in project monitoring improves public service delivery.